Apoplastic immunity and its suppression by filamentous plant pathogens. Issue 4 (17th April 2013) - Doehlemann, Gunther; Hemetsberger, Christoph
Summary: Microbial plant pathogens have evolved a variety of strategies to enter plant hosts and cause disease. In particular, biotrophic pathogens, which parasitize living plant tissue, establish sophisticated interactions in which they modulate the plant's metabolism to their own good. The prime decision, whether or not a pathogen can accommodate itself in its host tissue, is made during the initial phase of infection. At this stage, the plant immune system recognizes conserved molecular patterns of the invading microbe, which initiate a set of basal immune responses. Induced plant defense proteins, toxic compounds and antimicrobial proteins encounter a broad arsenal of pathogen‐derived virulence factors that aim to disarm host immunity. Crucial regulatory processes and protein–protein interactions take place in the apoplast, that is, intercellular spaces, plant cell walls and defined host–pathogen interfaces which are formed between the plant cytoplasm and the specialized infection structures of many biotrophic pathogens. This article aims to provide an insight into the most important principles and components of apoplastic plant immunity and its modulation by filamentous microbial pathogens.   Contents     Summary 1001 I. Live and let die – the basics of interaction 1001 II. A kettle of color – components of apoplastic plant defense 1003 III. A kettle of color – components of apoplastic plant defense 1004 IV. How they learned to live with the bomb – disarming proteases 1005 V. Hide and seek – how to survive the apoplast 1006 VI. Hide and seek – how to survive the apoplast 1007 VII. Back to the future – challenges and opportunities 1011   Acknowledgements 1011   References 1011